2016
DOI: 10.1590/abd1806-4841.20163643
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic action of protoporphyrin IX derivatives on Trichophyton rubrum

Abstract: BACKGROUNDDermatophytes are filamentous keratinophilic fungi. Trichophyton rubrum is a prevalent infectious agent in tineas and other skin diseases. Drug therapy is considered to be limited in the treatment of such infections, mainly due to low accessibility of the drug to the tissue attacked and development of antifungal resistance in these microorganisms. In this context, Photodynamic Therapy is presented as an alternative.OBJECTIVEEvaluate, in vitro, the photodynamic activity of four derivatives of Protopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Ramos et al [18] demonstrated in their study the Pp IX dimethyl ester obtained by derivatization of Pp IX in an analogous procedure described by Uchoa et al [86] . In the in vitro study by Ramos et al, Pp IX homogenized with T. rubrum was irradiated with blue LED ≈ 400 nm.…”
Section: Photodynamic Action Of the Photosensitizer Associated With V...mentioning
confidence: 94%
See 2 more Smart Citations
“…Ramos et al [18] demonstrated in their study the Pp IX dimethyl ester obtained by derivatization of Pp IX in an analogous procedure described by Uchoa et al [86] . In the in vitro study by Ramos et al, Pp IX homogenized with T. rubrum was irradiated with blue LED ≈ 400 nm.…”
Section: Photodynamic Action Of the Photosensitizer Associated With V...mentioning
confidence: 94%
“…The internalization of Pp IX in the cell resulted in photooxidative damage when irradiated with  of 400 nm, region in which this PS presents the band with the highest absorption intensity, the Soret band. The incorporation and internalization of PS in T. rubrum shows that the elimination of the fungal agent occurred by a photoinduced process, since this process is initiated by the transfer of hydrogens or electrons, radical reactions or electrophilic attack of singlet oxygen in cell membranes [18,87] .…”
Section: Photodynamic Action Of the Photosensitizer Associated With V...mentioning
confidence: 99%
See 1 more Smart Citation
“…Genus Trichophyton sp merupakan genus dengan persentase tertinggi penyebab kerusakan kuku. Pernyataan tersebut sejalan dengan pernyataan (Ramos et al, 2016) yang menyatakan dalam penelitiannya bahwa jamur dengan genus Trichophyton sp merupakan jamur yang sering menyebabkan dermatofitosis. Penelitian sebelumnya dari juga menjelaskan bahwa jamur Trichophyton sp merupakan genus terbesar penyebab dermatomikosis yaitu sebesar 64%.…”
Section: Berdasarkanunclassified
“…These fungi have an essential enzyme system to metabolize keratin, used as a substrate to obtain nutrients and energy. They are classified into three genera: Microsporum, Trichophyton and Epidermophyton [2][3][4].…”
Section: Introductionmentioning
confidence: 99%